The techniques of modern online journalism on sites of leading online media in Ukraine - Chabanenko, Myroslava V. (Journal of the Belarusian State University. Journalism, 2019)
The content of online media is an important area of research in recent years, which allows to discover and explore issues relating to transforming of methods and techniques of journalism under the influence of new media functioning. Using the methods of observation and comparative analysis a review of leading online media in Ukraine was implemented in order to identify the features of this segment of media market. The web sites, ranked first thirty places in the monthly ranking of po pularity according to the data of Internet Association of Ukraine, were reviewed. The attention was drawn to the genres and thematic variety, the speed of materials updates, usage of a hypertextuality, multimedia and interactivity, the quality of publications, approaches to the organization of information flows and some features of design. The comparison of publications from different headings on mentioned web sites has allowed to determine the extent of their compliance with the most mo dern requirements. It was find that, in the whole, Ukrainian Internet media reflect the general for all online journalism trends, which, in particular, are expressed in the active adaptation of text and other formats of media messages to the information space of the Internet. The results of this study confirm many previously known positions on the processes taking place in the media sphere, and may serve as inputs for further more detailed study of certain aspects of online journalism at the example of online media in different countries. They can also be used by practicing journalists to improve their professional activities.